ISSUE OF NON-DISCRIMINATION EDUCATIONAL AREA: CONTENT ANALYSIS OF COURSEBOOKS - Voyevutko, Natalia; Protsenko, Olena (The Modern Higher Education Review, 2020)
The article identifies the main components of content analysis of course-books on the principle of nondiscrimination. It is detailed the content of parameters to which it is expedient to carry out the anti-discriminatory examination of course-books, among them: pedagogical expedience, the content of text material, illustrative material and the language of course-book.